Genetic diversity study in B and R lines of rice (Oryza sativa L.) - Islam, MS; Mian, MAK; Rasul, MG (Bangladesh Journal of Plant Breeding and Genetics, 2011)
Bangladesh Journal of Plant Breeding and Genetics, Vol.22(2) December 2009 57-62